Perlindungan Hukum Terhadap Tertanggung Dari Perusahaan Asuransi Yang Dinyatakan Pailit - Ferial Fatimah; Siti Malikhatun Badriyah; Irawati Irawati (Magister Kenotariatan Universitas Diponegoro, 2021)
insurance is considered capable of protecting oneself from unexpected risks such as death. This article discusses the position of the insured and the legal protection of the insured if a life insurance company is declared bankrupt. This research uses normative juridical. Data collection techniques are carried out by literature studies and interviews with related informants, namely the curator. When an insurance company is declared bankrupt. The insured's legal position according to the Insurance Act, has a position